A Non‐Fullerene Acceptor with Chlorinated Thienyl Conjugated Side Chains for High‐Performance Polymer Solar Cells via Toluene Processing. Issue 7 (21st April 2020) - Li, Guangwei; Wu, Jingnan; Fang, Jin; Guo, Xia; Zhu, Lei; Liu, Feng; Zhang, Maojie; Li, Yongfang
Summary of main observation and conclusion: Small molecular acceptors (SMAs) BTC‐2F and BTH‐2F, based on heptacyclic benzodi(cyclopentadithiophene) electron‐donating core (CBT) with chlorinated‐thienyl conjugated and thienyl conjugated side chains, respectively, are designed and synthesized. Compared with non‐chlorine acceptor BTH‐2F, BTC‐2F exhibits slightly blue‐shifted absorption spectra, similar the lowest unoccupied molecular orbital (LUMO) (–3.91 eV), deeper highest occupied molecular orbital (HOMO) energy level and higher electron mobility than that of BTH‐2F. PM6, a wide bandgap polymer, is selected as the donor material to construct bulk heterojunction polymer solar cells processed with nonhalogenated solvent toluene. The optimized PM6:BTC‐2F‐based device presents a 12.9% power conversion efficiency (PCE), while the PCE of PM6:BTH‐2F‐based device is only 11.3%. The results suggest that it is an effective strategy to optimize the photoelectric properties of SMAs by incorporating chlorine atom into the conjugated side chains. Abstract : A new narrow bandgap small molecular acceptor (SMA) BTC‐2F with chlorine substituted on the conjugated side chains was synthesized. Power conversion efficiency (PCE) of 12.9% is obtained based on PM6:BTC‐2F device with nonhalogenated solvent.